صناعة التكافل الماليزية: عوامل النجاح ومكامن التطوير Malaysian Takaful Industry: Success Factors and Development Potentials - (Muhammad Akram Laluddin), محمد أكرم لال الدين; (Said Bouhrawa), سعيد بوهراوة (Journal of Islam in Asia (E-ISSN 2289-8077), 2013)
اهتمت هذه الورقة بدراسة التجربة الماليزية في التأمين التعاوني، وهو ما يصطلح عليه في ماليزيا بالتكافل، وعرض أهم محطاتها، وبيان أهم عوامل نجاحها من خلال تحليل أهم إنجازاتها على مستوى البنية التحتية والإطار القانوني وإسهاماتها في خدمة العملاء، وكذا أهم عوائقها والجوانب التي تحتاج إلى تحسين وتطوير. والهدف من هذه الورقة هو محاولة رفد التأمين الإسلامي بتجربة متميزة من خلال تثمين جهود التجربة الماليزية المبذولة، والاستفادة من أهم إنجازاتها وجوانب قوتها، وتلافي مواطن ضعفها. الكلمات المفتاحية: صناعة التكافل الماليزي، التأمين التكافلي ، شركات التكافل ـ إعادة التأمين التكافلي ـ قانون التكافل الماليزي. ************************************ This research is focused on the study of Malaysian experience in the cooperative insurance, which is termed in Malaysia as takaful. The study presents the most crucial stations of the industry; states its most significant success factors through the analysis of its most crucial achievements at the level of infrastructure, the legal framework, and its contributions to customer service; and it also states its big barriers and various aspects that are in need of improvement and development. This study is an attempt to supplement the Islamic insurance with the Malaysian experience by valuing its efforts, learning from its most important achievements, and strengths and weaknesses. Keywords: Malaysian Takaful industry, Takaful insurance, Takaful companies, Takaful reinsurance, Malaysian Takaful Act.